Outward FDI by Indian manufacturing MNEs: Impacts and implications - Khanindra Ch. Das (Asia-Pacific Research and Training Network on Trade (ARTNeT), 2015)
Outward foreign direct investment (OFDI) by Indian firms has increased significantly in recent years. Such investments by Indian firms have gone to more than 100 host countries. However, little is known about the effects of such OFDI on domestic activity of Indian multinational enterprises (MNEs). The paper investigates the home-country effects of OFDI by Indian manufacturing firms during 2008/09 to 2011/12 using a quasi-experimental technique. A priori, the relationship between firm's OFDI and domestic activity is ambiguous as both complementary and substitution effects could be induced by such investment activities. The propensity score matching technique is used, to construct treatment and control groups, for examining the effect of engaging in OFDI on domestic activities of Indian manufacturing MNEs. The empirical evidence suggests that OFDI by Indian MNEs has positive impact on export intensity and research and development (R&D). On the other hand, no significant impact could be found on domestic investments, output, employment, import of raw materials, and import of capital goods. Overall, no significant negative (or substitution) effect of OFDI on domestic activity could be discerned in this study. Nevertheless, to derive desired complementary benefits of OFDI by the manufacturing firms, policies may be directed to enhance the country's international supply chain connectivity for greater participation in global value chain and production network.
Keywords: F13; F14; F21; F23; O31; 330; Outward FDI; Multinational Enterprises; Manufacturing; Propensity Score Matching; Production Network